СПРОБА ПРАВОГО ПЕРЕВОРОТУ В УНР НАВЕСНІ 1919 РОКУ (Zaporizhzhia Historical Review, 2021)
The article is devoted to one of the worst irradiated events in the history of the Ukrainian right parties during the period of the Directoire of the Ukrainian popular republic. On a solid base of hammered sources the author discloses motives, character and consequences of marching of the opposition on the 29th of April 1919 in Rivne and the inwardness of the atamanís movement. Despite the historiography of the Ukrainian popular republic in which this revolution was identified with a manifestation of atamanís power the author considers the actions of the rights as a governmental orientation with constructive propositions of taking the country out of crisis.